ONLINE PEER ASSESSMENT UNTUK MENGEMBANGKAN KETERAMPILAN PRESENTASI ORAL DISKUSI KELOMPOK KECIL PADA PEMBELAJARAN IPS - Segara, Nuansa Bayu; Hermansyah, Hermansyah (Universitas Pendidikan Indonesia, 2019)
One goal of developing soft skills in the social studies class on higher education student is communication skill. This article explains how to effect peer assessment to developing communication skill, especially oral presentation in the small group discussion. The subject in this research is 51 students Faculty Education of Universitas Swadaya Gunung Djati Cirebon who contract social studies class. The research design is an experimental study. The design consisted of two groups an experimental and control. Instruments used to measure an oral presentation is a valid and reliable rubric, can be accessed online. Based on the result of research, there is a significant effect on online peer assessment to oral presentation skill in the small group discussion. Students have a role to be a respectable assessor. They assess the oral presentation colleagues objectively and authentic. Online peer assessment is useful for the assessment process. Besides that, students obtain feedback for improving oral presentation performance.